Using the Steel-Vessel Material-Cost Index to Mitigate Shipbuilder Risk - Keating, Edward G. (RAND Corporation, 2008)
The more accurately a cost index captures a shipbuilder's risk, the less the Navy should have to pay its shipbuilders. The Navy uses such indexes to correct for significant cost risks outside its shipbuilders' control. A longtime material-cost index in Navy shipbuilding is the steel-vessel index, but it is outdated and volatile. The authors urge the Navy to develop a modern-vessel index that more appropriately represents the materials used today.